ANALISIS SIMBOL DAN MAKNA MANTRA DALAM TRADISI BERASAH MASYARAKAT DESA RIAM BUNUT KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Devi Kusmarini; Christanto Syam; Antonius Totok Apriadi (Universitas Tanjungpura, 2019)
AbstractThis research conducted by a willing to analyze more about symbol and meaning sharpened spell that is a legacy for generation by forefathers. A common problem in this research is the symbol and meaning of the mantra of sharpened Ketapang local village, with a specific problem that is the symbol of the mantra sharpened, spells sharpened meaning, and implementation in schools. The method used in this research is descriptive method with qualitative research. Based on thes analysis, it is concluded that the symbols contained in the mantra of sharp Ketapang villages Local distric of the sound of 45 symbols, the following symbols: symbols Basmalah, black charcoal, blood, flesh, bone, father, mather, all, fatahan-fatahan, pontak-panting, loose tongue, loose teeth, nur, turak-turak, solar, Lailahailallah, white foam, black, decay, fertile, sindi, asalamualaikum, nur liah, life, holy, clear, sitting, chair, siti, teacher, mountain, xylophone, wind, water, seribuji, selamun sani, kamang, bute, selewah, word, kodrat, liuk, rahman, rahim, and show. The meaning contained in the honed mantra is the religious meaning and the meaning of personality, the results implemented for the world of education in learning Indonesian to the VIII SMP student 2013 curriculum odd semester. Keywords: Meaning, Sharp Spells, Symbol.